Enhancing sulfate-rich wastewater treatment through polyvinyl alcohol -immobilized sulfidogenic granules: Optimization of reactor configuration and bioaugmentation strategies - Rebeca Castro; Lorenz Adrian; Gemma Gabriel; David Gabriel; Xavier Gamisans; Xavier Guimerà (Journal of Environmental Chemical Engineering, 2026)

Development of a flow-cell bioreactor for immobilized sulfidogenic sludge characterization using electrochemical H2S microsensors - Rebeca Castro; Gemma Gabriel; David Gabriel; Xavier Gamisans; Xavier Guimerà (Chemosphere, 2024)

The effect of slime accumulated in a long-term operating UASB using crude glycerol to treat S-rich wastewater - Xudong Zhou; Eva Fernández-Palacios; Antoni D. Dorado; Javier Lafuente; Xavier Gamisans; David Gabriel (Journal of Environmental Sciences, 2024)

Mass transfer vectors for nitric oxide removal through biological treatments - David Fernando Cubides Páez; Xavier Guimerà Villalba; Nerea Abasolo Zabalo; Helena Torrell Galceran; Irene Jubany Güell; Xavier Gamisans Noguera (Environmental Science and Pollution Research, 2023)
The reduction of nitric oxide (NO) emissions to atmosphere has been recently addressed using biological technologies. However, NO removal through bioprocesses is quite challenging due to the low solubility of NO in water. Therefore, the abatement of NO emissions might be improved by adding a chelating agent or a mass transfer vector (MTV) to increase the solubility of this pollutant into the aqueous phase where the bioprocess takes place. This research seeks to assess the performance of different non-aqueous phase liquids (NAPs): n-hexadecane (HEX), diethyl sebacate (DSE), 1,1,1,3,5,5,5-heptamethyl-trisiloxane (HTX), 2,2,4,4,6,8,8-heptamethylnonane (HNO), and high temperature silicone oil (SO) in chemical absorption–biological reduction (CABR) integrated systems. The results showed that HNO and HTX had the maximum gas-liquid mass transfer capacity, being 0.32 mol NO/kmol NAP and 0.29 mol NO/kmol NAP, respectively. When an aqueous phase was added to the system, the mass transfer gas–liquid of NO was increased, with HTX reaching a removal efficiency of 82 ± 3% NO with water, and 88 ± 6% with a phosphate buffer solution. All NAPs were tested for short-term toxicity assessment and resulted neither toxic nor inhibitory for the biological activity (denitrification). DSE was found to be biodegradable, which could limit its applicability in biological processes for gas treatment. Finally, in the CABR system tests, it was shown that NO elimination improved in a short time (30 min) when the three mass transfer vectors (HEX, HTX, HNO) were added to enriched denitrifying bacteria.

A review: Biological technologies for nitrogen monoxide abatement - David Cubides; Xavier Guimerà; Irene Jubany; Xavier Gamisans (Chemosphere, 2023)

A novel bioscrubber for the treatment of high loads of ammonia from polluted gas - Eloi Morral; Antonio D. Dorado; Xavier Gamisans (Environmental Science and Pollution Research, 2022)

Optimization of SO2 and NOx sequential wet absorption in a two-stage bioscrubber for elemental sulphur valorisation - Xavier Guimerà; Mabel Mora; Antonio David Dorado; Anna Bonsfills; David Gabriel; Xavier Gamisans (Environmental Science and Pollution Research, 2021)

Exploring Arsenic Adsorption at low Concentration onto Modified Leonardite - Montserrat Solé-Sardans; Xavier Gamisans; Antonio David Dorado; Conxita Lao-Luque (Water, Air, & Soil Pollution, 2016)

Characterization of chromium (III) removal from aqueous solutions by an immature coal (leonardite). Toward a better understanding of the phenomena involved - Conxita Lao-Luque; Montserrat Solé; Xavier Gamisans; César Valderrama; Antonio D. Dorado (Clean Technologies and Environmental Policy, 2014)